Sucking and Gnawing Pests of Industrial Cannabis (Cannabis Sativa L.) - Makhliyo, Sharofboeva; kizi, Kahramon; Elmurod, Umurzakov (American Journal of Biomedicine and Pharmacy, 2025)
The article provides information on the biological characteristics, distribution, development and reproduction of some sucking and rodent pests of the technical cannabis plant. At the same time, the negative impact of pests on increasing the economic value of the cannabis plant is also highlighted. Peach aphids, heteroptera, cotton bollworms, thrips, spider mites, and grasshoppers, particularly common in cannabis, are briefly described.